Nonlinear deterministic sea wave prediction using instantaneous velocity profiles. (15th January 2021) - Huchet, Marion; Babarit, Aurélien; Ducrozet, Guillaume; Gilloteaux, Jean-Christophe; Ferrant, Pierre
Abstract: Optimizing the production of wave energy converters using Model Predictive Control (MPC) requires a real-time, deterministic prediction of the waves arriving at the device. This study presents a new method for deterministic sea wave prediction, using the horizontal velocity profile over the water column as a boundary condition for a dedicated nonlinear wave model. However, direct measurement of the horizontal velocity component over the whole vertical column is hardly achievable at sea. A method to reconstruct this profile from measurement devices currently at use, such as ADCPs, is thus presented and evaluated. The performance of the prediction method itself is then tested using synthetic numerical data. First, the reconstruction of the horizontal velocity profile as a boundary condition is evaluated. Then, the whole prediction procedure is assessed. In both these stages, the simulations are based on synthetic numerical data and the outcomes are compared with numerical reference solutions. The results show that the method is promising enough to justify further investigation through wave tank experiments. Highlights: A new method for deterministic sea wave prediction is proposed. It is based on an efficient wave propagation model and uses velocity measurements. The method is evaluated with realistic, synthetic numerical data as reference. Prediction remains accurate even for high steepness wave cases.